Pengaruh Pelayanan Prima Terhadap Tingkat Kepuasan Masyarakat di Satuan Lalu Lintas Polres Luwu Utara: Studi Empiris: Penelitian - Iqbal Wirawan Kasim; Nurmillah; Ali Imran (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
The excellent service implemented by the North Luwu Police Traffic Unit refers to excellent service that is satisfaction oriented. This excellent service is in the form of physical evidence (tangible) shown, reliability (reliability), responsiveness (responsiveness) to complaints, guarantee (assurance) for the service and empathy (empathy) provided. This research uses a quantitative approach. The research population and sample were 100 people who received services at the North Luwu Police Traffic Unit. Research instruments include observation, interviews, questionnaires and documentation. Data analysis uses multiple linear regression analysis. The research results found that excellent service has been implemented in the North Luwu Police Traffic Unit. Excellent service is based on the dimensions of service quality in the form of physical evidence (tangible), reliability, responsiveness, assurance and empathy to meet the level of community satisfaction to obtain quality service. The results of multiple linear regression analysis found that excellent service variables consisting of physical evidence (tangible), reliability, responsiveness, assurance and empathy have a significant effect on the level of community satisfaction in the Traffic Unit. North Luwu Police. This means that people have received services that suit their desires, needs and expectations.